2022
DOI: 10.1371/journal.pgen.1010561
|View full text |Cite
|
Sign up to set email alerts
|

The PilT retraction ATPase promotes both extension and retraction of the MSHA type IVa pilus in Vibrio cholerae

Abstract: Diverse bacterial species use type IVa pili (T4aP) to interact with their environments. The dynamic extension and retraction of T4aP is critical for their function, but the mechanisms that regulate this dynamic activity remain poorly understood. T4aP are typically extended via the activity of a dedicated extension motor ATPase and retracted via the action of an antagonistic retraction motor ATPase called PilT. These motors are generally functionally independent, and loss of PilT commonly results in T4aP hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Two bacterial species, Caulobacter crescentus and Vibrio cholerae, are also known to lack a retraction ATPase and it was shown that the assembly ATPase PilB is responsible for both pilus assembly and retraction (Ellison et al, 2017;Ellison et al, 2019;Hughes et al, 2022). In our case, it is likely that the adhesion pili assembly ATPase AapE also coordinates pilus retraction.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Two bacterial species, Caulobacter crescentus and Vibrio cholerae, are also known to lack a retraction ATPase and it was shown that the assembly ATPase PilB is responsible for both pilus assembly and retraction (Ellison et al, 2017;Ellison et al, 2019;Hughes et al, 2022). In our case, it is likely that the adhesion pili assembly ATPase AapE also coordinates pilus retraction.…”
Section: Discussionmentioning
confidence: 54%
“…For many years PilT was thought to be essential for retraction of type IV pili, leading to the proposal that archaeal pili are not capable of retraction and do not employ twitching motility (Chaudhury et al, 2018;Denise et al, 2019;Beeby, 2019). Recent work, however, has revealed the existence of PilT-independent retraction mechanisms in at least some bacteria (Ellison et al, 2017;Ellison et al, 2019;Hughes et al, 2022). While performing live-cell, time-lapse imaging of S. acidocaldarius at their normal growth temperature (75°C) we observed a type of surface-motility reminiscent of bacterial twitching motility (Charles-Orszag et al, 2021), challenging the idea that type IV pili in these cells are unable to retract.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, bacterial Tad pili are thought to have been acquired from archaea through horizontal gene transfer 29 . In the bacterial pathogen Vibrio cholerae , PilT promotes both pilus assembly and retraction 32 . Finally, type IV pili of the bacterial pathogen Neisseria gonorrhoeae exhibit slow, ATPase-independent retraction, which can be enhanced by PilT homologs 43 .…”
Section: Discussionmentioning
confidence: 99%
“…For many years PilT was thought to be essential for retraction of type IV pili, leading to the proposal that archaeal pili are not capable of retraction and do not employ twitching motility 3,28,29 . Recent work, however, revealed that some bacteria exhibit PilT-independent pilus retraction [30][31][32] . While performing livecell, time-lapse imaging of the model hyperthermophilic crenarchaeon Sulfolobus acidocaldarius at their normal growth temperature (75 °C) we previously observed a type of surface-motility reminiscent of bacterial twitching motility 33 , challenging the idea that type IV pili in these cells are unable to retract.…”
mentioning
confidence: 99%